2022
DOI: 10.3389/fendo.2022.928508
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Plasma MicroRNA Levels Predict Risk of Developing Gestational Diabetes Mellitus

Abstract: AimsOur objective is to identify first-trimester plasmatic miRNAs associated with and predictive of GDM.MethodsWe quantified miRNA using next-generation sequencing in discovery (Gen3G: n = 443/GDM = 56) and replication (3D: n = 139/GDM = 76) cohorts. We have diagnosed GDM using a 75-g oral glucose tolerance test and the IADPSG criteria. We applied stepwise logistic regression analysis among replicated miRNAs to build prediction models.ResultsWe identified 17 miRNAs associated with GDM development in both cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In a study using next-generation sequencing to identify plasma miRNA markers in patients with GDM in early pregnancy, 17 miRNAs associated with GDM development were identified, which may be involved in the regulation of lipid metabolism and insulin sensitivity (IS). Among them, three miRNAs, hsa-miR-517a-3p|hsa-miR-517b-3p, hsa-miR-218-5p and hsa-let7a-3p, have comparable predictive ability to traditional GDM risk factors [ 54 ]. Another study observed that plasma miRNAs from 18 patients with early pregnancy GDM predicted IS in the late second trimester of pregnancy [ 55 ].…”
Section: Role Of Ncrnas In Gdmmentioning
confidence: 99%
“…In a study using next-generation sequencing to identify plasma miRNA markers in patients with GDM in early pregnancy, 17 miRNAs associated with GDM development were identified, which may be involved in the regulation of lipid metabolism and insulin sensitivity (IS). Among them, three miRNAs, hsa-miR-517a-3p|hsa-miR-517b-3p, hsa-miR-218-5p and hsa-let7a-3p, have comparable predictive ability to traditional GDM risk factors [ 54 ]. Another study observed that plasma miRNAs from 18 patients with early pregnancy GDM predicted IS in the late second trimester of pregnancy [ 55 ].…”
Section: Role Of Ncrnas In Gdmmentioning
confidence: 99%
“…Given their stability in blood and other body fluids, the utility of miRNAs as non-invasive biomarkers has been examined, including for GDM. An increasing area of interest is identifying circulating miRNAs that are present early in pregnancy and associated with the development of GDM and using these miRNAs to help predict the development of GDM [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. To date, many of the studies that have been performed have been small with limited power and have used different approaches to identify relevant miRNAs.…”
Section: Gdm and Epigeneticsmentioning
confidence: 99%
“…Together, studies seeking to identify miRNAs in the first trimester and early second trimester of pregnancy have identified 37 miRNAs associated with the development of GDM ( Table 3 ) [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. However, most of these miRNAs were specific to a single study and not reproduced in other studies.…”
Section: Gdm and Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations